Orientation Tuning of Cytochrome Oxidase Patches in Macaque Primary Visual Cortex - Economides, John R. (2011)
The abundant concentration of cytochrome oxidase in patches or blobs of primate striate cortex has never been explained. Patches are thought to contain unoriented, color-opponent neurons. Lacking orientation selectivity, these cells might endow patches with a high level of metabolic activity because they respond to all contours in visual scenes. To test this idea, orientation tuning was measured in layer 2/3 of macaque V1 using acutely implanted 100-electrode arrays. Each electrode recording site was identified, and assigned to the patch or interpatch compartment. The mean orientation bandwidth of cells was 28.4° in patches and 25.8° in interpatches. Neurons in patches were indeed less orientation selective, but the difference was subtle, indicating that the processing of form and color is not strictly segregated in V1. The most conspicuous finding was that patch cells had a 49% greater overall firing rate. This global difference in neuronal responsiveness, rather than an absence of orientation tuning, may account for the rich mitochondrial enzyme activity that defines patches.